Carbon and water dynamics of a bioenergy crop (Cynara cardunculus L.) under different meteorological conditions in a semi-arid region - Rana, Gianfranco; Ferrara, Rossana M.; Muschitiello, Cristina (Italian Journal of Agronomy, 2017)
To evaluate the environmental adaptability of cultivated cardoon (Cynara cardunculus L.) its water use efficiency [(WUE) – ratio between net ecosystem exchange (NEE) and evapotranspiration (ET)] was analysed. The crop was cultivated in South Italy and WUE was evaluated at different time scales during two seasons: wet and dry. Even if the crop development is similar in the two seasons, plants delay their development in the presence of drought, showing, in this way, an improvement in their adaptability. Seasonal WUE in the dry season is greater than in the wet one by +11.2%, and this is also confirmed at monthly and daily scale. Hourly analysis around the full development phase shows that WUE is greater during the wet season than during the dry one, this being explainable when considering the impact of the drivers [(photosynthetically active radiation (PAR), vapour pressure deficit (VPD), and air temperature (Tair)] on CO2 and H2O exchanges by stomatal regulation. The saturation values of NEE in function of PAR (threshold 2.5 MJ m–2h–1) and VPD (threshold 10 hPa) are greater during the wet season than the dry one. Furthermore, also the linear relationships between ET and PAR and VPD showed higher slopes in the wet season than in the dry one. Drought causes reduction in both photosynthesis and evapotranspiration by stomatal regulation, however, the photosynthesis process is surely more sensitive to water stress than the crop transpiration, thus demonstrating the good adaptability of this crop to scarce water availability of semi-arid conditions.